Pengembangan Sistem Informasi Pelayanan Kepegawaian Berbasis Web dengan Metode Waterfall - Kharisma, Kharisma; Usman, Saifudin; Vivianlai, Stevani; Reza, Muhammad (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Politeknik Negeri Ketapang (Politap) is a university that has a variety of employees who support the learning activity process. Polytap employees consisting of lecturers, technicians, education administration staff, cleaning staff and security staff make employee data management complex. an information system is needed as a forum for managing data on various employees at Politap so that information about employees in the Politap environment is quick and easy to access so that decisions for employees such as employee placement, promotion and salary are quickly handled. The staffing information system will be developed using web-based with the aim of facilitating and accelerating access to employee data by employees and staffing administration at Politap. The system development method used in this research uses the waterfall method, system design using Unified Modelling Language (UML), Hypertext Preprocessing (PHP) programming language with Structured Query Language (SQL) database. The final result of this research is a web-based Politap staffing information system that functions as a place to manage employee data at Politap which is easy and fast to access. The results of system testing using blackbox testing, each feature on the system was successfully tested and the system can run well.